The Urgency of Criminal Liability For Beneficial Owners In Corporations Based on Presidential Regulation No. 13 of 2018 - Eka Sumahendra, I Gede; Amrullah, M. Arief; Tanuwijaya, Fanny (Universitas Ekasakti, 2024)
The issue of accountability of beneficial owners despite juridical Article 6 paragraph 2 of the Anti-Money Laundering Law arises because Article 6 paragraph 2 of the Anti-Money Laundering Law does not provide clarity on whether beneficial owners can be considered as corporations, considering that beneficial owners are outside the corporate structure. The focus of the issue revolves around the criminal accountability of Beneficial Owners in Corporations if they engage in Money Laundering and efforts to prevent money laundering activities carried out by the beneficial owners of corporations based on Presidential Regulation No. 13 of 2018. The urgency of Presidential Regulation No. 13 of 2018 regarding the application of the principles of beneficial ownership in corporations in the prevention and eradication of money laundering is to provide transparency regarding the definition of beneficial owners, their position, policy principles, and objectives. The legal basis for the criminal accountability of beneficial owners in corporations related to money laundering faces a vacuum of regulations, making it difficult for law enforcement to establish a foundation focusing on beneficial owners as controllers of corporations, which is not accommodated in current law. This creates a legal loophole that allows them to engage in money laundering without criminal accountability.